Stock Picking and Market Timing of the Gulf Fund Managers: Evidence from the Financial Crisis - Elmesseary, Mohamed (European Journal of Sustainable Development, 2014)
From five Gulf countries over the 2007-2012 period, this paper offers a comprehensive investigation for these managerial skills during and after the Financial Crisis (FC) of 2007- 2008; it also inspects the relative differences in performance between equity conventional mutual funds (CMFS) and Islamic ones. The results show no evidence of over-or-under performance for the fund managers due to these two skills, where there are no structural changes for the regression line across the two sub-periods, but it reveals the superiority of equity CMFS performance in Kuwait in particular along the overall period. Thus, it seems that if the investors cannot gain superior returns by investing in the Gulf mutual funds on general, they may attain a comparative advantage by investing in the conventional funds against the Islamic ones especially in Kuwait. It also implies that the ethical screening, which is adopted by the Islamic funds of Kuwait, already limits their diversification opportunities and then adversely affects their performance. JEL classification: G1; G2 Keywords: Capital markets, Islamic mutual funds, performance evaluation, market timing ability, stock picking ability